Successful Antiviral Therapy Reduces Risk of Schizophrenia Among Chronic Hepatitis C Patients: A Nationwide Real-World Taiwanese Cohort (T-COACH). (31st August 2020) - Tsai, Pei-Chien; Chen, Chi-Yi; Kuo, Hsing-Tao; Hung, Chao-Hung; Tseng, Kuo-Chih; Lai, Hsueh-Chou; Peng, Cheng-Yuan; Wang, Jing-Houng; Chen, Jyh-Jou; Lee, Pei-Lun; Chien, Rong-Nan; Yang, Chi-Chieh; et al.
Abstract: Background: Chronic hepatitis C (CHC) has been associated with major psychoses, and interferon (IFN)-based therapy may cause psychiatric sequelae. We aimed to evaluate the effects of sustained virological response (SVR) on the incidence of major psychoses in a nationwide Taiwanese CHC cohort. Methods: Fifteen thousand eight hundred thirty-six CHC Taiwanese who received IFN-based therapy were enrolled between 2003 and 2015. Of those, 12 723 patients were linked to the National Health Insurance Research Databases for the incidence of major psychoses. Death before major psychoses was considered a competing risk. Results: Twenty-four patients developed new-onset major psychoses during 67 554 person-years (3.6 per 10 000 person-years), including 16 affective psychoses, 7 schizophrenia, and 1 organic psychotic condition. The incidence of major psychoses and affective psychoses did not differ between the SVR and non-SVR groups. The 10-year cumulative incidence of schizophrenia were significantly higher in the non-SVR than in SVR patients (0.14% vs 0.04%, P = .036). Cox subdistribution hazards showed that SVR and older age were associated with a significantly lower risk of schizophrenia (hazard ratio = 0.18 and 0.17). Sustained virological response was associated with decreased incidence of schizophrenia and majorly observed among patients with age <45 ( P = .02). Conclusions: Successful IFN-based therapy might reduce the incidence of schizophrenia among CHC patients, especially among younger patients.